75 Gbit/s transmission over single mode fibre links using 8‐PAM and 8‐AACC modulations. Issue 5 (1st March 2017) - Dong‐Nhat, N.; Nguyen, L.; Malekmohammadi, A.
Abstract : Absolute added correlative coding with eight levels has been proposed and demonstrated numerically at bit rates of 30 and 60 Gbps back‐to‐back, and up to 75 Gbps over 2000 and 3000 m standard single‐mode fibre using a single‐drive multiple quantum‐well Mach–Zehnder modulator. The transmission performance is compared with the conventional eight‐level pulse amplitude modulation.